Ontogenetic development and redescription of Oligonychus pratensis (Banks, 1912) (Acari: Tetranychidae) - Li, Juan; Yi, Tian-Ci; Guo, Jian-Jun; Jin, Dao-Chao (Zootaxa, 2018)
Oligonychus pratensis (Banks, 1912) is redescribed based on adult females as well as immature instars collected from Imperata (Poaceae) in Zhangjiajie City, Hunan Province, China. The ontogenetic development of chaetotaxy in O. pratensis is the same as that in O. afrasiaticus (McGregor, 1939) and O. saccharinus Baker & Pritchard, 1960. Moreover, we remove O. shinkajii Ehara, 1963 from synonymy with O. modestus (Banks, 1900), due to significant differences in their aedeagal morphology.